1971
DOI: 10.1042/bj1220298
|View full text |Cite
|
Sign up to set email alerts
|

Membranes of chromaffin granules. Isolation and partial characterization of two proteins

Abstract: Membranes of chromaffin granules were isolated from the adrenal glands of four different species. The solubilized membrane proteins could be resolved into several bands by polyacrylamide-gel electrophoresis (alkaline and acid gel systems). Two major protein components appeared to be common to the chromaffin granule membranes of ox, horse, pig and man. The various membrane proteins of bovine chromaffin granules were separated by filtration on Sephadex G-200 in the presence of sodium dodecyl sulphate. Two major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…The amino acid composition of this protein [75] is given in Table I. It is significantly different from that of chromogranin A.…”
Section: Properties Of Chromomembrin Bmentioning
confidence: 96%
See 2 more Smart Citations
“…The amino acid composition of this protein [75] is given in Table I. It is significantly different from that of chromogranin A.…”
Section: Properties Of Chromomembrin Bmentioning
confidence: 96%
“…Chromomembrin B is a major component of the membranes of chromaffin granules in the low molecular weight region [ll,23a,75,143;see Fig. 11.…”
Section: H R O M O M E M B R I N Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies performed in three granular systems other than the rabbit parotid--the guinea pig exocrine pancreas, the rat liver, and the bovine adrenal medulla--have given indication that removal of polypeptides known not to be membrane proteins to limiting levels of detectability has not been attained (47,37,26,68,70). In these studies the contaminating proteins are again secretory proteins identified by enzymatic activity, by comparative gel electrophoresis with soluble extracts of the fractions under investigation, or by a characteristic high rate of incorporation of radioactively tagged amino acid during pulse labeling.…”
Section: Castle Et Al Secretion Granules O F the Rabbit Parotid Glanmentioning
confidence: 99%
“…However, it remains unknown whether the proteins of the cell membrane translocate from the Golgi complex to cell membrane in association with secretory granules or some other vesicles. Biochemical analysis has revealed that the secretory granule membrane usually had a simpler polypeptide composition on SDS ,-PAGE than that of the cell membrane (1,8,16,26,28,34,38). Recently, Kelly and Moore et al (18,29,31) demostrated two secretory pathways (i,e., "regulated" and "constitutive" pathways) in secretory cells and some cell membrane proteins may be transported from the Golgi trans face to the cell membrane accompanied by small vesicles but not by secretory granules.…”
Section: Preparation Of Mcabsmentioning
confidence: 99%